Lithium ion battery
By adding specific components to the nonaqueous electrolyte of the lithium-ion battery and adjusting its proportion, combined with optimizing the bonding force between the negative electrode material layer and the current collector, the problems of high impedance and poor circulation performance of the lithium-ion battery during the fast charging process are solved, and low impedance and excellent fast charging cycle performance are achieved.
Patent Information
- Application Number
- CN202510094440.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-01-21
AI Technical Summary
Existing lithium-ion batteries have problems of high impedance and poor cycle performance during fast charging, making it difficult to take into account low impedance and excellent fast charging cycle performance.
A non-aqueous electrolyte is used to contain lithium salts, organic solvents, sulfur-containing compounds, bisfluorophosphate ions and oxalate complex anions. By adjusting the proportion of these components and the bonding force between the negative electrode material layer and the current collector, an interface film rich in LiF and with low film impedance is formed.
It realizes the low impedance and excellent fast charging and cycling performance of lithium-ion batteries under high temperature conditions, ensuring the long-term stability and performance of the battery.
Smart Images

Figure BDA0005252467250000021 
Figure BDA0005252467250000091 
Figure BDA0005252467250000092
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a lithium-ion battery with fast charging cycle performance and relatively low impedance. Background Art
[0002] To limit the impact of climate change and air pollution, the widespread use of lithium-ion batteries in pure electric vehicles is accelerating. However, compared with traditional fuel vehicles, problems such as range anxiety and long charging time have become the main problems hindering the development of electric vehicles. Therefore, improving fast charging capabilities has become an urgent development goal for battery manufacturers and vehicle manufacturers.
[0003] Lithium-ion batteries are mainly composed of four key parts: positive electrode, negative electrode, electrolyte and separator. A large number of studies have shown that the attenuation of the positive electrode and the growth of the positive electrode CEI film have no effect on the fast charging speed of traditional lithium-ion systems. Therefore, the negative electrode, especially the lithium ion migration ability of the SEI interface film, has become a major research direction. Studies have shown that the chemical composition of the SEI film is closely related to the composition of the electrolyte. Based on the current conventional carbonate solvent and lithium hexafluorophosphate-based electrolyte system, the SEI film is close to the electrode interface inner layer with a stable and dense Li 2 CO 3 , Li 2 O, LiF and other inorganic substances, and the outer layer near the interface is composed of loose and porous ROLi, ROCO 2 Li and other organic substances. Among them, LiF is considered to be one of the key components affecting the stability of the interfacial film. 2 F 2 ) and the adjustment of other components of the electrolyte can change the abundance of LiF in the interface film to achieve better high-temperature performance. However, as an inorganic component, LiF itself does not have good lithium ion migration ability. Many papers point out that the distribution of the components of the SEI film presents the characteristics of a "mosaic model", and the migration of lithium ions in the inner interface film is achieved by the migration of different component interfaces. Among them, LiF / Li 2 CO 3 The interface is a key feature that affects the ionic conductivity of the interfacial membrane. More LiF interfaces will significantly reduce the membrane impedance and thus improve the fast charging capability of lithium-ion batteries. Therefore, developing a lithium-ion battery that can form a LiF-rich and low membrane impedance is of great significance for balancing battery impedance and excellent fast charging cycle performance. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a lithium-ion battery with excellent fast charging cycle performance and low impedance.
[0005] The present invention adopts the following technical solutions:
[0006] A lithium ion battery comprising a positive electrode, a negative electrode and a non-aqueous electrolyte;
[0007] The negative electrode comprises a negative electrode current collector and a negative electrode material layer arranged on the surface of the negative electrode current collector;
[0008] The non-aqueous electrolyte comprises a lithium salt, an organic solvent, a sulfur-containing compound, a difluorophosphate ion and an oxalate complex anion;
[0009] The sulfur-containing compound includes at least one of the following compounds:
[0010]
[0011] The lithium-ion battery meets the following conditions:
[0012] 0.05≤a / c≤15, 0.05≤b / (c×d)≤20; and 0.01≤a≤1, 0.01≤b≤1.2, 0.01≤c≤0.8, 0.5≤d≤15;
[0013] Wherein, a is the mass percentage of sulfur-containing compounds in the non-aqueous electrolyte, in wt%;
[0014] b is the mass percentage of difluorophosphate ions in the non-aqueous electrolyte, in wt%;
[0015] c is the mass percentage of oxalate complex anions in the non-aqueous electrolyte, in wt%;
[0016] d is the bonding force between the negative electrode material layer and the negative electrode current collector, in N / m, and is tested by the national standard GB / T2790-1995 adhesive 180° peel strength test method.
[0017] The lithium ion battery of the present invention uses a sulfur-containing compound as an additive in the non-aqueous electrolyte, and contains difluorophosphate ions and oxalate complex anions. The inventor has found through extensive research that when the mass percentage a of the sulfur-containing compound in the non-aqueous electrolyte, the mass percentage b of the difluorophosphate ions, the mass percentage c of the oxalate complex anions, and the bonding force d between the negative electrode material layer and the negative electrode current collector meet the relationship of 0.05≤a / c≤15, 0.05≤b / (c×d)≤20; and 0.01≤a≤1, 0.01≤b≤1.2, 0.01≤c≤0.8, 0.5≤d≤15, the battery can take into account both low initial impedance and excellent high-temperature fast-charge cycle performance. It is speculated that the oxalate complex anions, as electrolyte additives, can reduce impedance. On the one hand, due to its low film-forming potential, most of the oxalate complex anions can participate in the film formation in advance, and the fluorinated oxalate complex anions can increase the abundance of LiF in the interface film. More importantly, the presence of the oxalate structure can form more Li 2 CO 3 Components, when used in combination with difluorophosphate ions, can significantly increase the abundance of LiF and have a higher LiF / Li 2 CO 3 interface, so that the lithium-ion battery has both impedance and excellent high-temperature performance; on the other hand, the oxalate complex anion usually has a ring structure, which enables it to complex with the transition metal ions dissolved from the positive electrode, thereby reducing the damage of the metal ions to the SEI film and the catalytic decomposition of the electrolyte, inhibiting the impedance growth and ensuring the long-term performance of the battery.
[0018] Although the oxalate complex anion plays an important role in regulating membrane components, Li 2 CO 3 The components have poor oxidation resistance and may be converted into CO or CO under high voltage. 2 , resulting in separation of the pole pieces or a decrease in the bonding force between the negative electrode material layer and the negative electrode current collector, resulting in uneven lithium insertion in the battery or hindered conduction of electrons between the negative electrode material layer and the current collector. In addition, the addition of oxalate complex anions in the battery's electrolyte increases the acidity of the electrolyte, which may attack the interface film or corrode the negative electrode current collector, deteriorating battery performance.
[0019] In view of this problem, the inventors have found through extensive research that the negative electrode manufacturing process can be adjusted to have a higher initial bonding force to offset the negative impact of the subsequent reduction in bonding force between the negative electrode material layer and the negative electrode current collector. 2 CO 3 components, but at the same time, more sulfur-containing components and components similar to polyethylene oxide (PEO) structure can be generated, which have better stability and can reduce Li 2 CO 3The decomposition gas is generated, and it has a strong binding effect with fluoride ions to inhibit the growth and negative effects of HF. The film-forming potential of sulfur-containing compounds is higher than that of difluorophosphate ions and oxalate complex anions, that is, it forms a film later, protecting the stability of other film-forming components, while improving the toughness of the outer layer of the inorganic film and reducing the film damage caused by the volume change of the electrode during the cycle. Therefore, the lithium-ion battery of the present invention controls the formation of a low-impedance and more stable negative electrode interface film by utilizing the film-forming order and component characteristics of different substances, and combines the pre-control of the formation of a higher negative electrode material layer and the negative electrode current collector to offset the degradation of the negative electrode by micro-gas production, and finally achieves both the impedance of the battery and the fast charging cycle performance.
[0020] When the relationship between the mass percentage a of the sulfur-containing compound in the non-aqueous electrolyte and the mass percentage c of the oxalate complex anion is less than 0.05, it means that the content of the sulfur-containing compound is too little or the oxalate complex anion in the electrolyte is too much; if the a value is too small, it is difficult to suppress the negative effect of the oxalate complex anion participating in the film formation, the battery gas production increases and the impedance grows rapidly; if the c value is too large, not only can its negative effect be suppressed, but even because of the earliest Li in the interface film of its film formation, the battery gas production increases and the impedance grows rapidly. 2 CO 3 If there is too much, the proportion of LiF will decrease and the film-forming effect of difluorophosphate will not be prominent.
[0021] When the relationship between the mass percentage a of the sulfur-containing compound in the non-aqueous electrolyte and the mass percentage c of the oxalate complex anion is a / c>15, it means that the content of the sulfur-containing compound is too high or the oxalate complex anion in the electrolyte is too low; if the a value is too large, although a highly stable, dense and uniform film can be formed, the impedance of the positive and negative electrode membranes is too large, which aggravates the heat generation of the battery and the transmission kinetics of lithium ions in the interface film are poor. The battery is prone to lithium precipitation during fast charging, resulting in rapid reaction and consumption of the electrolyte and active lithium; if the c value is too small, the compound film formation of difluorophosphate ions and sulfur-containing compounds may result in good stability but large impedance, or low impedance and poor stability, and it is impossible to take into account both impedance and high temperature performance.
[0022] Preferably, the relationship between the mass percentage a of the sulfur-containing compound and the mass percentage c of the difluorophosphate ion in the non-aqueous electrolyte satisfies 0.1≤a / c≤10.
[0023] When the relationship between the mass percentage of difluorophosphate ions, the mass percentage of oxalate complex anions, and the bonding force between the negative electrode material layer and the negative electrode current collector in the non-aqueous electrolyte is b / (c×d)<0.05, it means that the difluorophosphate ions are too few or the oxalate complex anions are too much or the bonding force between the negative electrode material layer and the negative electrode current collector is too large. If the b value is too small, it is difficult to form an interface film rich in LiF and the film stability is poor; if the c value is too high, the film stability is also poor and the battery is prone to gas production and the impedance increases rapidly; if the d value is too large, it means that the amount of negative electrode binder used is too much or is enriched on the surface, which is not conducive to the electronic conduction of the negative electrode and even affects the film formation stability. At the same time, it will cause the performance of the negative electrode active material to be unable to be fully exerted, and the actual capacity is manifested as a low capacity at the battery level.
[0024] When the relationship b / (c×d)>20, it means that there are too many difluorophosphate ions or too little oxalate complex anion content or too low adhesion between the negative electrode material layer and the current collector. If the c value is too low, the battery impedance cannot be effectively reduced, and it is difficult to meet the performance requirements of low impedance and fast charging cycle of the battery. If the b value is too large, it means that too much difluorophosphate-containing additives have been added. Too much LiF component will also deteriorate the impedance, and the additive may be LiPO 2 F 2 precipitates in the form of solid impurities, causing battery performance degradation; a too low d value may significantly increase the negative electrode ohmic impedance, increase battery polarization and cause fast charge cycle degradation.
[0025] Preferably, the relationship among the mass percentage b of difluorophosphate ions in the non-aqueous electrolyte, the mass percentage c of oxalate complex anions, and the bonding force d between the negative electrode material layer of the negative electrode and the negative electrode current collector satisfies 0.1≤b / (c×d)≤5.
[0026] The sulfur-containing compound in the lithium-ion battery of the present invention can participate in forming a dense and uniform interface film at both the positive and negative electrodes, thereby improving the stability of the film and its tolerance to HF attack, thereby improving the high-temperature performance of the battery. In addition, it also has stronger and free F than proton H - The ability to combine can inhibit the generation of HF and the negative effect of destroying the interface film. Its film-forming potential is higher than that of difluorophosphate ions and oxalate complex anions, that is, its film-forming components are mainly distributed in the outer layer of the inorganic film, which protects the higher content of Li in the inner layer. 2 CO 3Avoid direct contact with liquid electrolyte reaction and gas production, while further improving the stability of the membrane and the toughness of the outer layer of the inorganic membrane, reducing membrane damage caused by changes in electrode volume during cycling. If the a value is too high, the battery impedance is too large, and the battery charge and discharge polarization and heat generation increase significantly, causing a series of negative effects such as thermal decomposition of lithium salts and impedance growth, and ultimately deteriorating the electrochemical properties of the battery. If the a value is too low, it is difficult to protect the inner layer of the inorganic membrane, which is rich in LiF and Li 2 CO 3 The component structure and the acidity growth problem caused by oxalate cannot be fully exerted. The film-forming effect of the oxalate complex anion cannot be suppressed and its gas production and acidity growth negative effects cannot be suppressed. Specifically, in some embodiments of the present invention, the mass percentage a of the sulfur-containing compound in the non-aqueous electrolyte is 0.01wt%, 0.03wt%, 0.05wt%, 0.08wt%, 0.1wt%, 0.15wt%, 0.2wt%, 0.25wt%, 0.3wt%, 0.35wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt% or the range of any two of these values; preferably, the mass percentage a of the sulfur-containing compound in the non-aqueous electrolyte is 0.05-0.5wt%.
[0027] The difluorophosphate ions in the non-aqueous electrolyte of the lithium ion battery of the present invention come from the hydrolysis of the compound containing difluorophosphate ions and the lithium salt lithium hexafluorophosphate. The difluorophosphate ions can participate in the formation of the SEI film, increase the content of LiF in the membrane components, and thus improve the stability of the SEI film and reduce the membrane impedance. If the b value is too high, the difluorophosphate ions are easy to precipitate from the electrolyte or cannot be completely dissolved, and as impurities and foreign matter, the internal force of the battery is uneven and the battery performance is deteriorated, and too high a content may cause excessive inorganic components in the interface film and deteriorate the battery impedance; if the b value is too low, it is difficult to form an interface film rich in LiF, and the battery impedance and high temperature performance cannot be improved. Specifically, in some embodiments of the present invention, the mass percentage b of difluorophosphate ions in the non-aqueous electrolyte is 0.01wt%, 0.03wt%, 0.05wt%, 0.08wt%, 0.1wt%, 0.15wt%, 0.2wt%, 0.25wt%, 0.3wt%, 0.35wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.1wt%, 1.2wt% or a range consisting of any two of these values; preferably, the mass percentage b of difluorophosphate ions in the non-aqueous electrolyte is 0.05-0.8wt%.
[0028] In the non-aqueous electrolyte of the lithium ion battery of the present invention, the mass percentage of difluorophosphate ions has the same meaning as the concentration of difluorophosphate ions; the method for determining the mass percentage of difluorophosphate ions is not particularly limited in the present invention, and a test method known in the art can be used, such as ion chromatography, 19 FNMR, etc.
[0029] The oxalate complex anions in the non-aqueous electrolyte of the lithium ion battery of the present invention participate in the film formation to generate more Li 2 CO 3 The components then work synergistically with difluorophosphate ions to not only generate LiF-rich interfacial film components, but also ensure sufficient LiF / Li 2 CO 3 The interface takes into account the low impedance of the battery. In addition, its film-forming potential is lower than that of difluorophosphate ions, sulfur-containing compounds, and most commonly used electrolyte additives, which makes it form Li 2 CO 3 The inorganic inner SEI film with gradient content changes has a gradient structure that can increase the Li 2 CO 3 While minimizing the Li in the inorganic outer layer that can contact the liquid electrolyte 2 CO 3 To prevent Li 2 CO 3 In addition, if the c value is too high, there will be too much Li in the SEI film. 2 CO 3 components and the electrolyte acidity increased significantly, Li 2 CO 3 It is easy to decompose and produce CO or CO at high temperature or high voltage. 2 Gas makes the electrode separation battery deintercalate and deintercalate lithium unevenly, and Li 2 CO 3The ability to isolate electrons is worse than that of LiF, which will generate a thicker SEI film in the formation stage and deteriorate the impedance. The increase in acidity will destroy the positive and negative electrode interface films and even corrode the electrode active materials, deteriorating the battery impedance and high temperature performance. If the c value is too low, the improvement in battery performance is very limited. Specifically, in some embodiments of the present invention, the mass percentage c of oxalate complex anions in the non-aqueous electrolyte of the lithium ion battery is 0.01wt%, 0.03wt%, 0.05wt%, 0.08wt%, 0.1wt%, 0.3wt%, 0.5wt%, 0.8wt% or a range consisting of any two of these values; preferably, the mass percentage c of oxalate complex anions in the non-aqueous electrolyte of the lithium ion battery is 0.05-0.5wt%.
[0030] In the non-aqueous electrolyte of the lithium ion battery of the present invention, the mass percentage of the oxalate complex anion has the same meaning as the concentration of the oxalate complex anion; the present invention does not specifically limit the method for determining the mass percentage of the oxalate complex anion, and a test method known in the art can be used, such as ion chromatography, 19 F NMR, etc.
[0031] In the negative electrode of the lithium ion battery of the present invention, too low bonding force between the negative electrode material layer and the negative electrode current collector will affect the electronic conduction between the negative electrode material layer and the negative electrode current collector, increase the impedance of the battery and the polarization during charge and discharge, and have a significant negative effect on the fast charge cycle performance of the battery and the charging capacity during fast charge. As the d value increases, the lower the barrier for electrons to pass through the interface between the negative electrode current collector and the negative electrode material layer, the faster the speed at which active ions and electrons exchange charges on the surface of the negative electrode active material will be, and the battery can have better kinetic performance. However, when the d value is too large, it means that there is too much binder content in the negative electrode material layer, or the binder is enriched on the surface of the negative electrode active material, or the spread area of the binder on the negative electrode current collector is too large, which is not conducive to the electronic conduction of the negative electrode and even affects the film formation stability. The dynamics and cycle performance of the battery are significantly deteriorated. At the same time, too much binder content in the negative electrode material layer will also affect the actual capacity of the battery. Specifically, in some embodiments of the present invention, the bonding force d between the negative electrode material layer and the negative electrode current collector is 0.5 N / m, 0.8 N / m, 1 N / m, 1.1 N / m, 1.2 N / m, 1.3 N / m, 1.4 N / m, 1.5 N / m, 1.8 N / m, 1.9 N / m, 2.0 N / m, 2.1 N / , 2.2 N / m, 2.5 N / m, 2.6 N / m, 2.8 N / m, 2.9 N / m, 3.0 N / m, 3.1 N / m, 3.2 N / m, 3.3 N / m, 3.5 N / m, 3.6 N / m, 3.8 N / m, 4.0 N / m, 4.1 N / m, 4.2 N / m, 4.5 N / m, 4 .6N / m, 4.8N / m, 5N / m, 5.1N / m, 5.2N / m, 5.5N / m, 5.6N / m, 5.8N / m, 6.0N / m, 6.5N / m, 7.0N / m, 7.5N / m, 8.0N / m, 8.5N / m, 9.0N / m, 9.5N / m, 10N / m, 11N / m, 12N / m, 13N / m, 14N / m, 14.5N / m, 15N / m or a range consisting of any two of these values; preferably, the bonding force d between the negative electrode material layer and the negative electrode current collector is 1 to 5N / m; more preferably, the bonding force d between the negative electrode material layer and the negative electrode current collector is 1 to 3N / m.
[0032] Therefore, only the mass percentage of sulfur-containing compounds in the non-aqueous electrolyte, the difluorophosphate ion [PO 2 F 2 -] the mass percentage b, the mass percentage c of the oxalate complex anion in the non-aqueous electrolyte and the bonding force d between the negative electrode material layer and the negative electrode current collector of the negative electrode satisfy 0.05≤a / c≤15, 0.05≤b / (c×d)≤20; and 0.01≤a≤1, 0.01≤b≤1.2, 0.01≤c≤0.8, 0.5≤d≤15, in order to make full use of the characteristics of the three substances before and after film formation and the film-forming components, and combine the pre-control to form a higher bonding force between the negative electrode material layer and the negative electrode current collector to offset the degradation of it caused by micro-gas production, avoid the separation of the negative electrode material layer and the current collector, achieve the best membrane stability while maintaining low impedance, make up for their respective shortcomings, and make the battery have low impedance and excellent high temperature fast charging cycle performance.
[0033] Specifically, in some embodiments of the present invention, the oxalate complex anion is selected from at least one of difluorooxalatoborate ion, bisoxalatoborate anion, and difluorobisoxalatophosphate ion. In the non-aqueous electrolyte of the present invention, as counter ions of the oxalate complex anion, monovalent cations and divalent cations can be used; preferably, the monovalent cations are preferably lithium ions, sodium ions, and potassium ions, and the divalent cations are preferably magnesium ions and calcium ions. Other monovalent or divalent cations are also within the scope of protection of the present invention.
[0034] Specifically, in some embodiments of the present invention, the compound containing difluorophosphate ions is selected from at least one of lithium difluorophosphate, sodium difluorophosphate, potassium difluorophosphate, calcium difluorophosphate, and magnesium difluorophosphate. In the non-aqueous electrolyte of the present invention, as counter ions of difluorophosphate ions, monovalent cations and divalent cations can be used; preferably, the monovalent cation is preferably a lithium ion, and the divalent cation is preferably a magnesium ion. Other monovalent or divalent cations are also within the scope of protection of the present invention and will not be described in detail herein.
[0035] Specifically, in some embodiments of the present invention, the lithium salt further comprises lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), LiPO 2 F 2 , LiBF 4 、LiBOB、LiSbF 6 、LiAsF 6 、LiCF 3 SO 3 、LiDFOB、LiDFOP、LiN(SO 2 CF 3 ) 2 、LiC(SO 2 CF 3 ) 3 、LiN(SO 2 C2 F 5 ) 2 、LiCl、LiBr、LiI、LiClO 4 , LiB 10 Cl 10 、LiAlCl 4 , lithium chloroborane, lithium lower aliphatic carboxylate having 4 or less carbon atoms, and lithium tetraphenylborate.
[0036] Specifically, in some embodiments of the present invention, the organic solvent includes at least one of a cyclic carbonate solvent, a linear carbonate solvent, a carboxylate solvent, and an ether solvent.
[0037] In some preferred embodiments, the cyclic carbonate solvent includes at least one of vinylene carbonate, propylene carbonate, ethylene carbonate and butylene carbonate.
[0038] In some preferred embodiments, the linear carbonate solvent includes at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and methyl propyl carbonate.
[0039] In some preferred embodiments, the carboxylate solvent includes at least one of methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, methyl butyrate, methyl isobutyrate, methyl trimethylacetate and ethyl trimethylacetate.
[0040] In some preferred embodiments, the ether solvent includes at least one of ethylene glycol dimethyl ether, 1,3-dioxolane and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.
[0041] Specifically, in some embodiments of the present invention, the additive further includes an auxiliary additive, and the auxiliary additive includes at least one of cyclic sulfate compounds, sultone compounds, cyclic carbonate compounds, phosphate compounds, borate compounds and nitrile compounds.
[0042] In some preferred embodiments, the cyclic sulfate ester compound includes at least one of 4-methylvinyl sulfate, vinyl sulfate, and propylene sulfate.
[0043] In some preferred embodiments, the sultone compound includes at least one of 1,3-propane sultone, 1,4-butane sultone, and propenyl-1,3-sultone.
[0044] In some preferred embodiments, the cyclic carbonate compound includes at least one of vinylene carbonate, ethylene carbonate, methylene carbonate, fluoroethylene carbonate, trifluoromethylethylene carbonate, bisfluoroethylene carbonate and the compound shown in the following structural formula 1:
[0045]
[0046] In the structural formula 1 shown, R 21 , R 22 , R 23 , R 24 , R 25 , R 26 Each is independently selected from a hydrogen atom, a halogen atom, and a C1-C5 group;
[0047] In some preferred embodiments, the compound represented by structural formula 1 includes at least one of the compounds represented by compounds 1-1 to 1-6 below:
[0048]
[0049] In some preferred embodiments, the phosphate compound includes at least one of the compounds shown in the following structural formula 2:
[0050]
[0051] In the structural formula 2, R 31 , R 32 , R 33 Each independently selected from a saturated hydrocarbon group, an unsaturated hydrocarbon group, and a halogenated hydrocarbon group of C1-C5; more preferably, the compound shown in structural formula 2 includes at least one of tripropargyl phosphate, dipropargyl methyl phosphate, dipropargyl ethyl phosphate, dipropargyl propyl phosphate, dipropargyl trifluoromethyl phosphate, dipropargyl-2,2,2-trifluoroethyl phosphate, dipropargyl-3,3,3-trifluoropropyl phosphate, dipropargyl hexafluoroisopropyl phosphate, triallyl phosphate, diallyl methyl phosphate, diallyl ethyl phosphate, diallyl propyl phosphate, diallyl trifluoromethyl phosphate, diallyl-2,2,2-trifluoroethyl phosphate, diallyl-3,3,3-trifluoropropyl phosphate, and diallyl hexafluoroisopropyl phosphate.
[0052] In some preferred embodiments, the borate ester compound includes at least one of tris(trimethylsilyl)borate and tris(triethylsilyl)borate.
[0053] In some preferred embodiments, the nitrile compound includes at least one of succinonitrile, glutaronitrile, ethylene glycol bis(propionitrile) ether, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebacononitrile.
[0054] In some embodiments, based on the total mass of the non-aqueous electrolyte as 100%, the content of the auxiliary additive is 0.01wt% to 10wt%. Specifically, the content of any one of the optional substances in the auxiliary additive can be 0.01wt%, 0.05wt%, 0.08wt%, 0.1wt%, 0.5wt%, 0.8wt%, 1wt%, 1.2wt%, 1.5wt%, 1.8wt%, 2wt%, 2.2wt%, 2.5wt%, 2.8wt%, 3wt%, 3.2wt%, 3.5wt%, 3.8wt%, 4wt%, 4.5wt%, 5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt%, 8.5wt%, 9wt%, 9.5wt%, 10wt% or a range consisting of any two of these values.
[0055] Specifically, in some embodiments of the present invention, the negative electrode material layer includes a negative electrode active material, and the negative electrode active material includes one or more of soft carbon, hard carbon, artificial graphite, natural graphite, intermediate phase microcarbon beads, silicon, silicon oxides, silicon-carbon composites or metallic lithium.
[0056] Specifically, in some embodiments of the present invention, the negative electrode material layer further includes a negative electrode binder and a negative electrode conductor.
[0057] The negative electrode binder includes polyvinylidene fluoride, copolymers of vinylidene fluoride, polytetrafluoroethylene, copolymers of vinylidene fluoride-hexafluoropropylene, copolymers of tetrafluoroethylene-hexafluoropropylene, copolymers of tetrafluoroethylene-perfluoroalkyl vinyl ether, copolymers of ethylene-tetrafluoroethylene, copolymers of vinylidene fluoride-tetrafluoroethylene, copolymers of vinylidene fluoride-trifluoroethylene, copolymers of vinylidene fluoride-trichloroethylene, copolymers of vinylidene fluoride-fluoroethylene, copolymers of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, thermoplastic polyimide, thermoplastic resins such as polyethylene and polypropylene; acrylic resin; and one or more of styrene butadiene rubber.
[0058] The negative electrode conductive agent includes one or more of conductive carbon black, conductive carbon balls, conductive graphite, conductive carbon fibers, carbon nanotubes, graphene or reduced graphene oxide.
[0059] Specifically, in some embodiments of the present invention, the negative electrode current collector includes a metal material that can conduct electrons. Preferably, the negative electrode current collector includes one or more of aluminum, nickel, tin, copper, and stainless steel.
[0060] Specifically, in some embodiments of the present invention, the positive electrode includes a positive electrode material layer, the positive electrode material layer includes a positive electrode active material, and the positive electrode active material may include LiFe 1-x’ M' x’ PO 4 、LiMn 2-y’ M y’ O 4 and LiNi x Co y Mn z M 1-x-y-z O 2 One or more of, wherein M' is selected from one or more of Mn, Mg, Co, Ni, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, Zr, W, V or Ti, M is selected from one or more of Fe, Co, Ni, Mn, Mg, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, Zr, W, V or Ti, and 0≤x'<1, 0≤y'≤1, 0≤y≤1, 0≤x≤1, 0≤z≤1, x+y+z≤1, the positive electrode active material may also include one or more of sulfide, selenide, and halide. More preferably, the positive electrode active material may include LiCoO 2 、LiFePO 4 、LiFe 0.4 Mn 0.6 PO 4 、LiMn 2 O 4 、LiNi 0.5 Co 0.2 Mn 0.3 O 2 、LiNi 0.6 Co 0.2 Mn 0.2 O 2 、LiNi 0.7 Co 0.1 Mn 0.2 O 2 、LiNi 0.8 Co 0.1 Mn 0.1 O 2 、LiNi 0.8 Co 0.15 Al 0.05 O 2 、LiNi 0.9 Co 0.05 Mn 0.05 O 2 、LiNi 0.5 Co 0.2 Mn 0.2 Al 0.1 O2 、LiNi 0.5 Co 0.2 Al 0.3 O 2 One or more of .
[0061] Specifically, in some embodiments of the present invention, the positive electrode further comprises a positive electrode current collector, and the positive electrode material layer is disposed on the surface of the positive electrode current collector. The material of the positive electrode current collector may be the same as that of the negative electrode current collector, which will not be described in detail herein.
[0062] Specifically, in some embodiments of the present invention, the positive electrode material layer further includes a positive electrode binder and a positive electrode conductor, and the positive electrode active material, the positive electrode binder and the positive electrode conductor are blended to obtain the positive electrode material layer. The positive electrode binder and the positive electrode conductor may be the same as the negative electrode binder and the negative electrode conductor, respectively, and will not be described in detail here.
[0063] In the lithium-ion battery of the present invention, a separator is provided between the positive electrode and the negative electrode. The separator may be an existing conventional separator, such as a ceramic separator, a polymer separator, a non-woven fabric, an inorganic-organic composite separator, etc., including but not limited to single-layer PP (polypropylene), single-layer PE (polyethylene), double-layer PP / PE, double-layer PP / PP and triple-layer PP / PE / PP separators.
[0064] The non-aqueous electrolyte of the lithium ion battery of the present invention uses a sulfur-containing compound as an additive, and limits the relationship between the mass percentage a of the sulfur-containing compound in the non-aqueous electrolyte, the mass percentage b of the difluorophosphate ion, the mass percentage c of the oxalate complex anion, and the negative electrode material layer and the negative electrode current collector d of the battery to 0.05≤a / c≤15, 0.05≤b / (c×d)≤20; and 0.01≤a≤1, 0.01≤b≤1.2, 0.01≤c≤0.8, 0.5≤d≤15, which can give full play to the advantages of the oxalate complex anion in reducing the battery impedance and forming a highly stable LiF-rich interface film, and at the same time regulate the bonding force between the negative electrode material layer and the negative electrode current collector to offset the Li 2 CO 3 The impact of decomposition of gas production on the battery is achieved by utilizing the film formation order of different substances and the characteristics of the components to control the formation of a low-impedance and stable negative electrode interface film. Combined with the pre-control of the formation of a higher bonding force between the negative electrode material layer and the negative electrode current collector, the degradation of the battery caused by micro-gas production is offset, thus achieving a high-quality lithium-ion battery that takes into account both impedance and fast charging cycle performance. DETAILED DESCRIPTION
[0065] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention.
[0066] In the examples and comparative examples of the present invention, one of the compounds shown in Table 1 is used as a non-aqueous electrolyte additive.
[0067] Table 1
[0068]
[0069]
[0070] Example 1
[0071] The method for preparing a lithium-ion battery in this embodiment comprises the following steps:
[0072] 1) Preparation of positive electrode sheet:
[0073] LiNi 0.5 Mn 0.3 Co 0.2 O 2 , conductive carbon black Super-P and binder polyvinylidene fluoride (PVDF) are mixed evenly in a mass ratio of 97:1.5:1.5, and then dispersed in N-methyl-2-pyrrolidone (NMP) to obtain positive electrode slurry. The slurry is evenly coated on both sides of the aluminum foil, and after drying, rolling and vacuum drying, a positive electrode material layer is obtained, and an aluminum lead wire is welded with an ultrasonic welder to obtain a positive electrode sheet.
[0074] 2) Preparation of negative electrode sheet:
[0075] Weigh each material according to the negative electrode sheet ratio of graphite (Shanghai Shanshan, FSN-1): conductive carbon (superP): sodium carboxymethyl cellulose (CMC): styrene-butadiene rubber (SBR) = 96.3:1.0:1.2:1.5 (mass ratio); then add CMC into pure water at a solid content of 1.5%, stir for 120 minutes until uniform, and prepare a transparent CMC glue solution; add conductive carbon (superP) to the CMC glue solution, stir for 90 minutes to prepare a conductive glue; continue to add graphite to the above conductive glue, stir evenly, and obtain the required negative electrode slurry; evenly coat the prepared negative electrode slurry on copper foil, dry, roll, die-cut or strip, and weld nickel lead wires with an ultrasonic welder to obtain a negative electrode sheet.
[0076] The bonding force between the negative electrode material layer and the negative electrode current collector is tested. The test method is as follows: The bonding force test between the negative electrode material layer and the negative electrode current collector can refer to the national standard GB / T2790-1995 Adhesive 180° Peel Strength Test Method. In the specific test, a high-speed rail tensile machine can be used to perform a 180° peeling force test at a peeling speed of 50 mm / min. The average peeling force collected when the negative electrode sheet with a length of 60 mm is completely peeled off from the negative electrode current collector is taken as the bonding force between the negative electrode material layer and the negative electrode current collector. The test results are filled in Table 2.
[0077] 3) Preparation of electrolyte:
[0078] Ethylene carbonate (EC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) were mixed at a mass ratio of EC:DEC:EMC=1:1:1, and then lithium hexafluorophosphate and additives were added, wherein the concentration of lithium hexafluorophosphate in the non-aqueous electrolyte was 1.02 mol / L, and the type and content of each additive are shown in Table 2.
[0079] 4) Preparation of diaphragm:
[0080] A three-layer isolation film of polypropylene, polyethylene and polypropylene is used with a thickness of 20μm.
[0081] 5) Battery assembly:
[0082] The prepared positive electrode sheet, negative electrode sheet and separator are assembled into a laminated soft-pack battery cell.
[0083] 6) Battery filling and formation
[0084] In a glove box with a dew point controlled below -40°C, the prepared electrolyte was injected into the battery cell, vacuum packaged, and left to stand for 72 hours. Then, the conventional formation of the first charge was carried out according to the following steps: 0.05C constant current charging for 180 minutes, 0.1C constant current charging for 120 minutes, 0.2C constant current charging for 120 minutes, secondary vacuum sealing, and then further full charging at a current of 0.2C (100% SOC), after being left at room temperature for 72 hours, full discharge at a current of 0.2C (0% SOC).
[0085] Examples 2-33 and Comparative Examples 1-31
[0086] This embodiment and comparative example are used to compare and illustrate the lithium ion battery disclosed in the present invention, including most of the operating steps in the above-mentioned embodiment 1, and the differences are: the composition and content of the additive in the non-aqueous electrolyte, and the bonding force between the negative electrode material layer of the battery negative electrode and the negative electrode collector, as shown in Table 2.
[0087] Table 2
[0088]
[0089]
[0090]
[0091]
[0092] Among them: LiODFP-lithium difluorobis(oxalate)phosphate, LiODFB-lithium difluorobis(oxalate)phosphate, LiBOB-lithium dioxalateborate, DTD-vinyl sulfate, PS-1,3-propane sultone, VC-vinylene carbonate.
[0093] The lithium ion batteries prepared in Examples 1-33 and Comparative Examples 1-31 were subjected to the following performance tests as follows:
[0094] 1. High temperature fast charging cycle performance test:
[0095] At 45°C, the lithium-ion battery prepared in the embodiment and comparative example was charged at a constant current and constant voltage rate of 1C (cut-off current 0.05C) and discharged at a rate of 1C for three cycles, and the capacity of the last week was taken as the initial 100% SOC capacity. After charging to 80% SOC at a constant current rate of 4C, it was fully charged at a constant current and constant voltage rate of 1C (cut-off current 0.05C), and discharged at a rate of 1C. A full charge and discharge cycle test was performed within the commonly used charge and discharge cut-off voltage of the corresponding system (for example, 3-4.2V for NCM523 / artificial graphite system) until the capacity of the lithium-ion battery decayed to 80% of the initial capacity, and the number of cycles was recorded.
[0096] 2. Internal resistance test at 0℃:
[0097] At room temperature (25°C), charge the battery with constant current to 50% of the battery capacity, then adjust the temperature to 0°C and maintain it for 6 hours.
[0098] 0.1C constant current charging for 10s and then resting for 40s; 0.1C constant current discharging for 10s and then resting for 40s, record the end voltage V1;
[0099] 0.2C constant current charging for 10s and then resting for 40s; 0.2C constant current discharging for 10s and then resting for 40s, record the end voltage V2;
[0100] 0.5C constant current charging for 10s and then resting for 40s; 0.5C constant current discharging for 10s and then resting for 40s, record the end voltage V3;
[0101] Draw a straight line with current as the horizontal axis and voltage as the vertical axis. The slope of the straight line is the 0℃ impedance.
[0102] (1) The test results of Examples 1-19 and Comparative Examples 4-24 are shown in Table 3.
[0103] Table 3
[0104]
[0105]
[0106] It can be seen from the test results in Table 3 that the lithium ion battery of the present invention uses a sulfur-containing compound as an additive, and further controls the mass percentage content a of the sulfur-containing compound in the non-aqueous electrolyte, the mass percentage content b of the difluorophosphate ion, the mass percentage content c of the oxalate complex anion, and the bonding force d between the negative electrode material layer and the negative electrode collector to satisfy 0.05≤a / c≤15, 0.05≤b / (c×d)≤20; and when 0.01≤a≤1, 0.01≤b≤1.2, 0.01≤c≤0.8, and 0.5≤d≤15, the lithium ion battery can take into account both low impedance and fast charging cycle performance.
[0107] It can be seen from the test results of Example 1 and Comparative Examples 4-24 that when any one or more of the mass percentage a of the sulfur-containing compound in the non-aqueous electrolyte, the mass percentage b of the difluorophosphate ion, the mass percentage c of the oxalate complex anion, and the adhesion d between the negative electrode material layer and the negative electrode current collector do not meet the specified range, or at least one of a / c and b / (c×d) is too large or too small, the low impedance and fast charging cycle performance of the lithium ion battery cannot be taken into account; it indicates that the mass percentage a of the sulfur-containing compound, the mass percentage b of the difluorophosphate ion, the mass percentage c of the oxalate complex anion, and the adhesion d between the electrode material layer and the negative electrode current collector have a strong correlation in reducing the impedance of the lithium ion battery and optimizing the fast charging cycle performance of the lithium ion battery.
[0108] In particular, from the comparison of the test results of Example 1 and Comparative Examples 17-20, it can be seen that if the bonding force d between the negative electrode material layer and the negative electrode current collector does not meet the limited range, the battery performance will be deteriorated to a certain extent. Because it is too large, it is not conducive to the conduction of negative electrode electrons and affects the effect and stability of the oxalate complex anion participating in the film formation, and too small will increase the battery impedance and polarization during charging and discharging. The change of d will also cause the change of the relationship b / (c×d), indicating that the bonding force between the negative electrode material layer and the negative electrode current collector is a synergistic effect with sulfur-containing compounds, difluorophosphate ions, and oxalate complex anions to affect the impedance and fast charging cycle performance of lithium-ion batteries.
[0109] (2) The test results of Examples 20-25 and Comparative Examples 25-28 are shown in Table 4.
[0110] Table 4
[0111]
[0112] It can be seen from the test results of Examples 20-25 and Comparative Examples 25-28 in Table 4 that for the lithium ion battery of the present invention, different positive electrode active materials are used. When the mass percentage content a of the sulfur-containing compound, the mass percentage content b of the difluorophosphate ion, the mass percentage content c of the oxalate complex anion, and the adhesion d between the negative electrode material layer and the negative electrode collector meet the corresponding conditions, the impedance performance and high temperature performance of the lithium ion battery can be optimized; under the same positive electrode active material, when any parameter of the mass percentage content a of the sulfur-containing compound, the mass percentage content b of the difluorophosphate ion, the mass percentage content c of the oxalate complex anion, and the adhesion d between the electrode material layer and the negative electrode collector does not meet the corresponding conditions, the battery performance will be affected; indicating that the battery system of the present invention is universal for different positive electrode active materials.
[0113] (3) The test results of Example 1, Examples 31-33 and Comparative Examples 29-31 are shown in Table 5.
[0114] Table 5
[0115]
[0116] It can be seen from the test results of Example 1 and Examples 31-33 in Table 5 that for the lithium ion battery of the present invention, when the non-aqueous electrolyte uses different tricyclic compounds as sulfur-containing compounds, when the mass percentage a of the sulfur-containing compound in the non-aqueous electrolyte, the mass percentage b of the difluorophosphate ion, the mass percentage c of the oxalate complex anion, and the adhesion d between the negative electrode material layer and the negative electrode current collector all meet the corresponding conditions, and the a / c, b / (c×d) relationship meets the corresponding conditions, the impedance performance and fast charge cycle performance of the lithium ion battery can be optimized. It can be seen from the test results of Example 1 and Comparative Examples 29-31 in Table 5 that when the sulfur-containing compound uses a compound with a bicyclic structure, it is impossible to suppress the deterioration of the battery performance by the lithium salt and the oxalate complex anion, and the impedance and fast charge cycle performance of the battery cannot be improved, which further illustrates the optimization effect of the tricyclic compound used in the sulfur-containing compound on the battery performance.
[0117] (4) The test results of Example 1 and Examples 26-27 are shown in Table 6.
[0118] Table 6
[0119]
[0120] It can be seen from the test results of Example 1 and Examples 26-27 in Table 6 that by using different compounds containing oxalate complex anions, when the mass percentage a of the sulfur-containing compound, the mass percentage b of the difluorophosphate ion, the mass percentage c of the oxalate acid complex anion, and the adhesion d between the negative electrode material layer and the negative electrode current collector meet the corresponding conditions, the impedance performance and high temperature performance of the lithium-ion battery can be optimized; this shows that the battery system of the present invention is universal for different compounds containing oxalate complex anions.
[0121] (5) The test results of Example 1, Examples 28-30, and Comparative Examples 1-3 are shown in Table 7.
[0122] Table 7
[0123]
[0124] From the test results of Example 1 and Examples 28-30 in Table 7, it can be seen that in the lithium ion battery of the present invention, the additional addition of additives such as vinyl sulfate (DTD), 1,3-propane sultone (PS), and vinylene carbonate (VC) to the non-aqueous electrolyte can further optimize the impedance performance and fast charge cycle performance of the lithium ion battery, indicating that there is a complementary effect between the additives of the present invention and other additives.
[0125] It can be seen from the test results of Example 1 and Comparative Examples 1-3 that when auxiliary additives are used in the non-aqueous electrolyte to replace sulfur-containing compounds or compounds containing oxalate complex anions, the additives cannot form a good synergistic effect, and the inhibition of lithium ion battery impedance growth and the improvement of fast charge cycle performance are not good. This shows that the lithium ion battery under the system of the present invention improves the impedance performance and fast charge cycle performance of the lithium ion battery by using specific additives and interacting with the adhesive force between the negative electrode material layer and the negative electrode current collector.
[0126] The present invention is further described above with the aid of specific embodiments. However, it should be understood that the specific description here should not be construed as limiting the essence and scope of the present invention. Various modifications made to the above embodiments by ordinary technicians in the field after reading this specification are all within the scope of protection of the present invention.
Claims
1. A lithium ion battery, characterized in that: including a positive electrode, a negative electrode and a non-aqueous electrolyte; The negative electrode comprises a negative electrode current collector and a negative electrode material layer arranged on the surface of the negative electrode current collector; The non-aqueous electrolyte comprises a lithium salt, an organic solvent, a sulfur-containing compound, a difluorophosphate ion and an oxalate complex anion; The sulfur-containing compound includes at least one of the following compounds: The lithium-ion battery meets the following conditions: 0.05≤a / c≤15, 0.05≤b / (c×d)≤20, 0.01≤a≤1, 0.01≤b≤1.2, 0.01≤c≤0.8, 0.5≤d≤15; Wherein, a is the mass percentage of sulfur-containing compounds in the non-aqueous electrolyte, in wt%; b is the mass percentage of difluorophosphate ions in the non-aqueous electrolyte, in wt%; c is the mass percentage of oxalate complex anions in the non-aqueous electrolyte, in wt%; d is the bonding force between the negative electrode material layer and the negative electrode current collector, in N / m, and is tested by the national standard GB / T2790-1995 adhesive 180° peel strength test method.
2. The lithium-ion battery according to claim 1, characterized in that The lithium ion battery satisfies: 0.1≤a / c≤10, 0.1≤b / (c×d)≤5.
3. The lithium-ion battery according to claim 1, characterized in that The mass percentage a of the sulfur-containing compound in the non-aqueous electrolyte is 0.05-0.5 wt %.
4. The lithium-ion battery according to claim 1, characterized in that: The mass percentage b of difluorophosphate ions in the non-aqueous electrolyte is 0.05-0.8 wt %.
5. The lithium-ion battery according to claim 1, characterized in that: The mass percentage c of the oxalate complex anion in the non-aqueous electrolyte is 0.05-0.5 wt %.
6. The lithium-ion battery according to claim 1, characterized in that The bonding force d between the negative electrode material layer and the negative electrode current collector is 1 to 5 N / m.
7. The lithium-ion battery according to claim 1, characterized in that: The oxalate complex anion is selected from at least one of difluorooxalatoborate anion, bisoxalatoborate anion, and difluorobisoxalatophosphate ion.
8. The lithium-ion battery according to claim 1, characterized in that The organic solvent includes one or more of cyclic carbonates, linear carbonates, carboxylates and ethers; and / or, The cyclic carbonate compound includes one or more of vinylene carbonate, propylene carbonate, ethylene carbonate and butylene carbonate; and / or, The linear carbonate comprises one or more of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and methyl propyl carbonate; and / or, The carboxylic acid ester includes one or more of methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, methyl butyrate, methyl isobutyrate, methyl trimethylacetate and ethyl trimethylacetate; and / or, The ethers include one or more of ethylene glycol dimethyl ether, 1,3-dioxolane and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.
9. The lithium-ion battery according to claim 1, characterized in that: The non-aqueous electrolyte further includes an auxiliary additive, wherein the auxiliary additive includes at least one of a cyclic sulfate compound, a sultone compound, a cyclic carbonate compound, a phosphate compound, a borate compound and a nitrile compound; and / or, Based on the total mass of the non-aqueous electrolyte being 100%, the content of the auxiliary additive is 0.01% to 10%; and / or, The cyclic sulfate ester compound includes at least one of 4-methylvinyl sulfate, vinyl sulfate, and propylene sulfate; and / or, The sultone compound includes at least one of 1,3-propane sultone, 1,4-butane sultone and propenyl-1,3-sultone; and / or, The cyclic carbonate compound includes at least one of vinylene carbonate, ethylene carbonate, methylene carbonate, fluoroethylene carbonate, trifluoromethylethylene carbonate, bisfluoroethylene carbonate and the compound shown in the following structural formula 1: In the structural formula 1 shown, R 21 , R 22 , R 23 , R 24 , R 25 , R 26 Each is independently selected from a hydrogen atom, a halogen atom, a C1-C5 group; and / or, The phosphate compound includes at least one of the compounds shown in the following structural formula 2: In the structural formula 2, R 31 , R 32 , R 33 Each independently selected from a C1-C5 saturated hydrocarbon group, an unsaturated hydrocarbon group, a halogenated hydrocarbon group; and / or, The borate compound includes at least one of tris(trimethylsilyl)borate and tris(triethylsilyl)borate; and / or, The nitrile compound includes at least one of succinonitrile, glutaronitrile, ethylene glycol bis(propionitrile) ether, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebaconitrile.
10. The lithium ion battery according to claim 1, characterized in that: The negative electrode material layer includes a negative electrode active material, and the negative electrode active material includes one or more of soft carbon, hard carbon, artificial graphite, natural graphite, mesophase micro carbon beads, silicon, silicon-oxygen compounds, silicon-carbon composites or metallic lithium.
Citation Information
Patent Citations
Lithium ion battery
CN117117324A
Non-aqueous electrolyte and secondary battery
CN117477027A
Electrolyte additive, electrolyte and electrochemical device
CN118486898A
Secondary battery and electronic device
CN118507844A
Non-aqueous electrolyte solution and secondary battery
WO2024016897A1
Cited By
Lithium ion battery
CN120073075A